Measurement of mass and width of the excited charmed meson states D10 and D2*0 at CDF - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
We report on precision measurements of the masses and widths of the narrow, orbitally excited states D10 and D2*0 using the CDF II detector at the Fermilab Tevatron. Both states (collectively called D**) are reconstructed in the decay channel D**→D*+π-. The D2*0 is also reconstructed in the D**→D+π- channel. Using a data set with an integrated luminosity of 210pb-1, the measured masses and widths for the D10 are 2421.7±0.7±0.6 MeV/c2 and 20.0±1.7±1.3 MeV/c2 respectively, while for the D2*0 they are 2463.3±0.6±0.8 MeV/c2 and 49.2±2.3±1.2 MeV/c2. These values are currently the single best measurements available. © 2006 The American Physical Society.